2000
DOI: 10.1002/(sici)1096-9071(200006)61:2<228::aid-jmv9>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Expression of caspid protein VP1 for use as antigen for the diagnosis of enterovirus 71 infection

Abstract: To produce enterovirus 71 antigen for diagnostic purposes, the gene encoding the entire capsid protein VP1 was amplified by reverse transcription-polymerase chain reaction (RT-PCR), cloned and expressed in Escherichia coli as a poly-histidine fusion protein. Western blotting experiments with sera from patients with enterovirus 71 infection indicated that immunoglobulin G (IgG) and IgM antibodies bound to a single polypeptide VP1. According to these results, IgM anti-VP1 appeared in sera of patients with a symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…In the present study, purified N protein of NDV, and VP1 protein of EV71 were used to determine murine IgG responses, as measured by ELISA and Western blot analyses. The potential of the individual N (Makkay et al, 1999) and VP1 proteins (Shih et al, 2000) as diagnostic agents has been evaluated. In our study, a recombinant N-VP1 fusion protein, namely Nt-VP1t was used.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, purified N protein of NDV, and VP1 protein of EV71 were used to determine murine IgG responses, as measured by ELISA and Western blot analyses. The potential of the individual N (Makkay et al, 1999) and VP1 proteins (Shih et al, 2000) as diagnostic agents has been evaluated. In our study, a recombinant N-VP1 fusion protein, namely Nt-VP1t was used.…”
Section: Discussionmentioning
confidence: 99%
“…Total DNA-free RNA was extracted from the prototype EV71 2272-infected cells using TRIzol reagent-chloroform (GibcoBRL) extraction as described earlier [14]. The concentration of RNA was determined spectrophotometrically at 260/280 nm and quality as assessed by visualization on an ethidium stained agarose gel.…”
Section: Construction Of Plasmidsmentioning
confidence: 99%
“…RT-PCR for cDNA synthesis and amplification was performed in a single step by adding RNA template and primers to RT-PCR beads (Amersham Pharmacia Biotech, Buckinghamshire, UK) containing MmuLV reverse transcriptase, RNase inhibitor, buffer, nucleotides, and taq polymerase. Two PCR oligodeoxynucleotide primers were synthesized as described earlier [14]; however, an NcoI and a HindIII restriction endonuclease site were introduced to allow ligation of the entire VP1 cDNA into pKK233-2, a prokaryotic expression vector with Salmonella-specific in vivo-regulated promoter [15] (Fig. 1A).…”
Section: Construction Of Plasmidsmentioning
confidence: 99%
“…It was shown that serum samples from patients infected with ENV71 recognise linear epitopes of a recombinant VP1, [19] indicating that these epitopes are immunogenic when a productive infection is progressing in vivo. The fi nding of our study is also in line with these reports.…”
Section: Resultsmentioning
confidence: 99%